Foreign aid, governance and economic development in Nepal - Sharma, Kishor (2011)
This article contributes to the aid effectiveness debate using Nepal as a case study, a country which has failed to accelerate growth and reduce poverty and inequality despite being a significant aid recipient for over half a century. The weak aid absorption capacity and lack of commitment to institutional reform appear to be the reasons for aid ineffectiveness. Nepal needs to embark on major reforms in governance, institutions and policy aimed at rural development. The commitment of donors to give more aid without fundamental reforms in these areas will only enable the ruling elite to remain in power without achieving the objectives of helping the poor and disadvantaged groups who live in the rural and remote areas. - Reproduced.
Keywords: Economic and social development - Nepal; Foreign aid - Nepal; Foreign aid